Statistics demystified - Gibilisco, Stan (McGraw-Hill "Demystified" series., 2011)
This book is for anyone who has an interest in statistics and wants to learn more about it outside of a formal classroom setting. It can also be used by home-schooled students, tutored students, and those people wishing to change careers. The material is presented in an easy-to-follow way and can be best understood when read from beginning to end.